9x(x+9x)=

Simple and best practice solution for 9x(x+9x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x(x+9x)= equation:


Simplifying
9x(x + 9x) = 0

Combine like terms: x + 9x = 10x
9x(10x) = 0

Remove parenthesis around (10x)
9x * 10x = 0

Reorder the terms for easier multiplication:
9 * 10x * x = 0

Multiply 9 * 10
90x * x = 0

Multiply x * x
90x2 = 0

Solving
90x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '90'.
x2 = 0.0

Simplifying
x2 = 0.0

Take the square root of each side:
x = {0.0}

See similar equations:

| -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r | | v=25(30) | | -2x+17=8+x | | -12r-48=12 | | -(5-3x)-6(2x-4)=x+1 | | 24x^4=36x^3-12x^2/12x^2 | | 19+3c=40 | | 7log(4x-1)=14 | | 5b-5.25b+3=3.75 | | -4c+5=9 | | -12x^2/12x^2 |

Equations solver categories